Evaluating living donor kidney transplant rates: Are you reaching your potential?. Issue 4 (1st March 2017) - Matar, Abraham J.; Files, John; Burkholder, Ryan; Chin, Thomas; Angelis, Michael
Abstract: Background: Traditionally, living donor kidney transplant (LDKT) rate has been calculated as a percentage of total kidney transplant volume. We believe this calculation to be inherently flawed because the number of deceased donor kidney transplants has no bearing on the number of LDKT performed. We propose an alternative calculation of LDKT rate as a percentage of the number of new waitlist registrants. Methods: We evaluated 192 adult transplant centers in the United States with respect to their LDKT rate according to both the traditional and proposed calculations, using data from the scientific registry of transplant recipients between July 2014 and June 2015. Results: The median LDKT rate for every 100 new waitlist registrants was 12.3, compared to 27.9 for every 100 total kidney transplants. Based on our proposed calculation of LDKT rate, 16.7% of transplant centers were misevaluated when compared to the national mean using the traditional method. Conclusions: A new calculation of LDKT rate based on new waitlist registrants, and not total kidney transplants, is necessary to eliminate the bias associated with the traditional method, allowing for the identification of centers for improvement as well as each individual center's true potential based on their patient demographics.